2019
DOI: 10.1248/bpb.b18-00913
|View full text |Cite
|
Sign up to set email alerts
|

Adeno Associated Virus (AAV) as a Tool for Clinical and Experimental Delivery of Target Genes into the Mammalian Retina

Abstract: With an increasing number of identified causative genes, the widespread use of gene therapy is quickly becoming feasible. Once a target gene is selected, it is important to have a cell delivery method that is both specific and efficient. Cell type specificity and high efficiency is particularly important for the treatment of retinal degeneration, since viruses are efficient gene delivery vehicles for the nervous system, but often bring with them non-specific infections. In this review, we focus on adeno-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Intravitreal AAV2 injection induced transgene expression under control of the CMV promoter in RGCs as well as in other retinal cells. [38][39][40] We believe that the phenotypic changes observed in AAV2-infected retinas could be attributed primarily to altered expression of Cdkn2a or Cdkn2b in RGCs, as shown by the following results. First, a higher infection efficiency was found in RGCs than in other cell types in AAV2-infected retinas ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Intravitreal AAV2 injection induced transgene expression under control of the CMV promoter in RGCs as well as in other retinal cells. [38][39][40] We believe that the phenotypic changes observed in AAV2-infected retinas could be attributed primarily to altered expression of Cdkn2a or Cdkn2b in RGCs, as shown by the following results. First, a higher infection efficiency was found in RGCs than in other cell types in AAV2-infected retinas ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have reported that retinal cells, such as amacrine, bipolar, and horizontal cells, as well as RGCs express NMDA receptor subunits, and are potentially sensitive to NMDA. [38][39][40] Thus, NMDA-mediated loss of the retinal cells, other than RGCs, could induce RGC death as its secondary effect. However, intravitreal NMDA injection increased the number of TUNEL þ cells in the GCL earlier than in the INL and outer nuclear layer (ONL; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We intravitreally injected adult wild-type mice with recombinant adeno-associated viruses (rAAVs) containing neuron-specific expression cassettes for VEGFD (rAAV-VEGFD) 43,50 or as control, LacZ (rAAV-LacZ), with additional hemagglutinin (HA; for rAAV-VEGFD) or Flag (for rAAV-LacZ) tags to facilitate their detection. Intravitreal injection of rAAVs is a robust method used successfully to achieve long-lasting, stable gene delivery 52 and is under consideration in clinical trials. 53 rAAV-VEGFD has been previously used effectively to boost neuronal expression of VEGFD 43,50 and does not infect cells of the microvasculature ( Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…As a gene delivery tool, however, AAV continues to be exceptionally popular with genome engineers. This popularity stems from many factors including ease of use, but is highlighted by its inability to spread to other non-target tissues without a helper virus and by a large number of serotypes that permit the design of AAV-based gene delivery vectors to many mammalian organs with good degrees of specificity (see, for example: [49,50]).…”
Section: Aav Replication and Integrationmentioning
confidence: 99%